KONTRIBUSI PENDAPATAN USAHA TOKO KELONTONG TERHADAP TOTAL PENDAPATAN KELUARGA di DESA SINGKUP, KECAMATAN PASAWAHAN – KABUPATEN KUNINGAN - Akbari, Safitri; Suwandi, Suwandi; Turini, Turini; Eka Septian, Willy; Umar Fakhrudin, Mohammad (Jurnal Saintifik (Multi Science Journal), 2024)
Singkup Village. Pasawahan District – Kuningan Regency is a Village Fostered by the Academic Community of Catur Insan Cendekia University, Cirebon City. The purpose of this study was to conduct an assessment of how big the contribution of grocery shop business income is to total income in Singkup Village, Pasawahan District - Cirebon Regency. The research method that the authors use in this research is descriptive method. The population in this study were 42 heads of families, this research was a population study. Data collection techniques used in this study are observation, interviews, and documentation. The collected data is then analysed in tabular form (percentage). The results of this study indicate that: (1) the main occupation of the head of the Singkup Village family is as a farmer, construction worker, teacher, breeder, driver and private employee, (2) the average main income of the head of the Singkup Village family is Rp. 2,703,500 per month, (3) the average profit from the grocery shop business is Rp. 1,763,000.- per month, (4) the average percentage contribution of grocery shop business income to total family income is 39.47%. The contribution resulting from this research is to add insight to lecturers and students according to their field of knowledge, the campus has provided an analysis of the income contribution of grocery stalls in the Foster Village, especially those who have a grocery shop business in Singkup Village. The novelty of this research is the author's suggestion to grocery shop entrepreneurs to be able to increase their business income.